The concurrence of subacute cutaneous lupus erythematosus and hand‐foot syndrome in a patient undergoing capecitabine chemotherapy. (13th December 2014) - Li, Zhiming; Jiang, Nanyan; Xu, Yunsheng
Abstract: We describe an unusual case of subacute cutaneous lupus erythematosus concurrent with hand‐foot syndrome, apparently associated with capecitabine treatment. We hypothesise that subacute cutaneous lupus erythematosus and hand‐foot syndrome may occur in a novel overlap syndrome.